Low heat release alloy thermoplastic panel for aviation interior and preparation process thereof

CN122917468APending Publication Date: 2026-10-16ZHEJIANG SHUHE NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611248301.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]现有冲击改性剂多为碳氢结构或聚丁二烯类橡胶,极易燃烧,添加后虽能提升材料的断裂伸长率和冲击强度,却会严重破坏CPVC本征的阻燃性,导致复合材料整体热释放速率和总热释放量显著上升,难以同时满足航空内饰对低热释放和良好韧性的双重需求,为此,针对上述描述中提出的问题,本发明提出低热释放航空内饰用合金热塑板及其制备工艺

Benefits of technology

1.本发明通过在橡胶内核中引入甲基丙烯酰氧乙基磷酸酯和乙烯基三乙氧基硅烷,磷-硅协同作用使内核在受热初期即促进基体形成致密炭层;中间层通过笼型聚倍半硅氧烷与交联剂形成刚性的无机-有机杂化阻隔墙,有效抑制内核燃烧向基材蔓延;外壳的甲基丙烯酸缩水甘油酯所含环氧基团能够与CPVC分子链上的氯原子或端基羟基发生化学接枝反应,使改性剂与基体之间由物理共混转变为化学键合,这种结构设计使得冲击改性剂自身成为阻燃贡献体,而非阻燃损耗体,同时化学接枝消除了界面应力集中点,材料在受到拉伸或吸塑成型时应力能够均匀传递,避免了常规增韧体系中因界面脱粘而引发的早期开裂。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917468A_ABST
    Figure CN122917468A_ABST
Patent Text Reader

Abstract

The present application relates to alloy thermoplastic plate technical field, specifically to low heat release alloy thermoplastic plate for aviation interior and its preparation process, including the following raw materials: chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, polymethyl methacrylate, impact modifier, heat stabilizer, lubricant, processing aid, flame retardant synergist.The present application introduces methacryloyloxyethyl phosphate and vinyl triethoxysilane into the rubber core, and the phosphorus-silicon synergistic effect makes the core promote the formation of dense carbon layer in the early stage of heating;The intermediate layer forms a rigid inorganic-organic hybrid barrier wall through the cage type polysilsesquioxane and crosslinking agent, effectively inhibits the spread of the core combustion to the substrate;The epoxy groups contained in the glycidyl methacrylate of the shell can occur chemical grafting reaction with the chlorine atoms or end group hydroxyl on the molecular chain of CPVC, so that the modified agent and the matrix are changed from physical blending to chemical bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy thermoplastic sheet technology, specifically to low heat release alloy thermoplastic sheet for aerospace interiors and its preparation process. Background Technology

[0002] Aviation interior materials must meet stringent airworthiness and fire protection standards, such as FAR25.853 and CCAR25.853, requiring materials to have low heat release, low smoke toxicity, and high flame retardancy. Chlorinated polyvinyl chloride (CPVC) is considered one of the ideal substrates for thermoplastic sheets used in aviation interiors due to its high chlorine content, good intrinsic flame retardancy, and corrosion resistance. However, CPVC has high molecular chain rigidity, low melt strength, narrow processing window, and poor impact toughness, which limits its direct application.

[0003] To improve the processing fluidity and impact resistance of CPVC, existing technologies typically employ physical blending to add impact modifiers (such as acrylates, chlorinated polyethylene, methyl methacrylate-butadiene-styrene copolymers, etc.) and heat stabilizers (such as calcium zinc soap, organotin, etc.).

[0004] Existing impact modifiers are mostly hydrocarbon-structured or polybutadiene-based rubbers, which are highly flammable. Although their addition can improve the elongation at break and impact strength of the material, it will seriously damage the intrinsic flame retardancy of CPVC, resulting in a significant increase in the overall heat release rate and total heat release of the composite material. It is difficult to simultaneously meet the dual requirements of low heat release and good toughness for aerospace interiors. Therefore, in response to the problems mentioned above, this invention proposes an alloy thermoplastic sheet for low heat release aerospace interiors and its preparation process. Summary of the Invention

[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide a low heat release alloy thermoplastic sheet for aviation interior and its preparation process, so as to solve the problems mentioned in the background art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: Low heat release alloy thermoplastic sheet for aerospace interiors comprises the following raw materials in parts by weight: 100 parts chlorinated polyvinyl chloride, 20-40 parts polyvinyl chloride, 15-30 parts ABS, 5-15 parts methyl methacrylate-butadiene-styrene copolymer, 5-10 parts polymethyl methacrylate, 5-15 parts impact modifier, 3-10 parts heat stabilizer, 0.5-2 parts lubricant, 1-3 parts processing aid, and 2-4 parts flame retardant synergist; The impact modifier is prepared through the following steps: S1. Add sodium dodecylbenzenesulfonate emulsifier and ammonium persulfate initiator to deionized water, replace with nitrogen, raise the temperature to 65-75℃, add mixed monomers dropwise, react for 6-8 hours to obtain a nucleus emulsion; S2. Add cage-type polysilsesquioxane and trimethylolpropane trimethacrylate dropwise to the core emulsion, and keep the reaction at a warm temperature for 2-3 hours to obtain the core-encapsulated emulsion; S3. Add shell monomers composed of methyl methacrylate, glycidyl methacrylate and acrylic acid dropwise to the core-encapsulated emulsion, continue the reaction for 3-4 hours, demulsify, wash, and spray dry to obtain the impact modifier.

[0007] Furthermore, the heat stabilizer is prepared through the following steps: C1. In anhydrous tetrahydrofuran, hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone were added, and triethylamine was used as an acid-binding agent. The reaction was carried out at 50-55℃ for 10-12 h. Then mono-(6-p-toluenesulfonyl)-β-cyclodextrin was added, and the grafting reaction was carried out at 55-60℃ for 20-24 h to obtain grafted polyphosphazene. C2. The grafted polyphosphazene was dispersed in an ethanol-water mixed solvent, zinc chloride and lanthanum nitrate were added, the pH was adjusted to 6.5-7, and the complexation reaction was carried out at 65-70℃ for 5-6 h. Then pentaerythritol was added, and the mixture was stirred at 50-55℃ for 10-12 h. The intermediate product was obtained by filtration, washing and drying. C3. Mix the intermediate product with dithiodipropionic acid, melt and react at 75-80℃ for 30-40 minutes, then pulverize and sieve to obtain the heat stabilizer.

[0008] Furthermore, in step S1, the mass ratio of deionized water, sodium dodecylbenzenesulfonate emulsifier, ammonium persulfate initiator, and mixed monomers is 100:(2-5):(0.5-1.5):(25-45), and the mixed monomers are composed of butadiene, styrene, methacryloyloxyethyl phosphate, and vinyltriethoxysilane in a mass ratio of (60-80):(15-30):(2-8):1.

[0009] Furthermore, in step S2, the mass ratio of the core emulsion, cage-type polysilsesquioxane, and trimethylolpropane trimethacrylate is 100:(3-8):(1-4).

[0010] Furthermore, in step S3, the mass ratio of the core-encapsulated emulsion to the shell monomer is 100:(15-30), wherein the shell monomer is composed of methyl methacrylate, glycidyl methacrylate, and acrylic acid in a mass ratio of (12-15):(2-4):1.

[0011] Furthermore, in step C1, the mass ratio of anhydrous tetrahydrofuran, hexachlorocyclotriphosphazene, 4,4'-dihydroxydiphenyl sulfone, triethylamine, and mono-(6-p-toluenesulfonyl)-β-cyclodextrin is 100:(10-15):(15-25):(20-30):(5-12).

[0012] Furthermore, in step C2, the mass ratio of grafted polyphosphazene, ethanol-water mixed solvent, zinc chloride, lanthanum nitrate, and pentaerythritol is 1:(8-15):(0.1-0.3):(0.2-0.5):(0.5-1.5).

[0013] Furthermore, the mass ratio of the intermediate product to dithiodipropionic acid in step C3 is 1:(0.2-0.6).

[0014] Furthermore, a preparation process for the aforementioned low-heat-release alloy thermoplastic sheet for aerospace interiors includes the following steps: A1. Chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, and polymethyl methacrylate are put into a high-speed mixer and stirred for 1-2 minutes. Impact modifier, heat stabilizer, lubricant, processing aid, and flame retardant synergist are added and mixed. The mixed material is dried at 80-90℃ for 2-3 hours. The dried material is then put into an automatic mixing device and stirred at low speed for 5-10 minutes. The material mixed a second time is sent into a twin cone screw extruder for extrusion. A2. The extruded hot sheet material enters a three-roll calender, where a leather texture is pressed out according to product requirements. The embossed sheet material enters a cooling and shaping device to cool to room temperature. An edge trimming machine is used to remove the irregular rough edges on both sides of the sheet material to obtain a low-heat-release alloy thermoplastic sheet for aerospace interiors.

[0015] Furthermore, the temperatures of the three rollers in the three-roll calender are controlled as follows: the upper roller is 80-90℃, the middle roller is 70-80℃, and the lower roller is 60-70℃.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention introduces methacryloyloxyethyl phosphate and vinyltriethoxysilane into the rubber core. The synergistic effect of phosphorus and silicon promotes the formation of a dense carbon layer in the matrix in the early stage of heating. The intermediate layer forms a rigid inorganic-organic hybrid barrier wall with cage-like polysilsesquioxane and crosslinking agent, effectively inhibiting the spread of core combustion to the substrate. The epoxy groups contained in the glycidyl methacrylate of the outer shell can undergo chemical grafting reaction with the chlorine atoms or terminal hydroxyl groups on the CPVC molecular chain, changing the physical blending between the modifier and the matrix into chemical bonding. This structural design makes the impact modifier itself a flame retardant contributor rather than a flame retardant loser. At the same time, chemical grafting eliminates the stress concentration points at the interface, and the stress can be uniformly transmitted when the material is stretched or vacuum-formed, avoiding early cracking caused by interface debonding in conventional toughening systems.

[0017] 2. This invention utilizes polyphosphazene as a macromolecular backbone, which possesses excellent char-forming properties and thermal stability. The grafted β-cyclodextrin contains pentaerythritol within its cavity, which is slowly released under the processing heat field. This pentaerythritol can react with the conjugated double bonds formed after deHCl removal from CPVC, achieving self-repair of the molecular chain. The zinc ions coordinated to the side chains can preferentially coordinate with unstable chlorine atoms, inhibiting the initiation of deHCl removal, while lanthanum ions, as Lewis acids, can promote cross-linking and char formation. The synergy of these two components not only stabilizes the processing but also pre-constructs a protective char layer during subsequent heating. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the preparation process of the low heat release alloy thermoplastic sheet for aviation interiors in this invention; Figure 2 This is a schematic diagram of the preparation process of the impact modifier in this invention; Figure 3 This is a schematic diagram of the preparation process of the heat stabilizer in this invention. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] Please see Figures 1-3 The present invention provides a technical solution: Example 1: Low heat release alloy thermoplastic sheet for aerospace interiors, comprising the following raw materials: 1000g chlorinated polyvinyl chloride, 200g polyvinyl chloride, 150g ABS, 50g methyl methacrylate-butadiene-styrene copolymer, 50g polymethyl methacrylate, 50g impact modifier, 30g heat stabilizer, 5g lubricant, 10g processing aid, 20g flame retardant synergist.

[0021] I. Preparation of impact modifier: S1. Take 1000g of deionized water, 20g of sodium dodecylbenzenesulfonate, and 5g of ammonium persulfate and mix them evenly. After purging with nitrogen, heat the mixture to 65℃ and add 250g of mixed monomers (composed of butadiene, styrene, methacryloyloxyethyl phosphate, and vinyltriethoxysilane in a mass ratio of 60:15:2:1). React at a constant temperature for 6 hours to obtain a nucleus emulsion.

[0022] S2. Add 30g of cage-type polysilsesquioxane and 10g of trimethylolpropane trimethacrylate to 1000g of nuclear emulsion, and keep the reaction at the temperature for 2h to obtain a nuclear-encapsulated emulsion.

[0023] S3. Add 150g of shell monomer (composed of methyl methacrylate, glycidyl methacrylate and acrylic acid in a mass ratio of 12:2:1) to 1000g of core-encapsulated emulsion, continue the reaction for 3h, and then demulsify, wash and spray dry to obtain the impact modifier.

[0024] II. Preparation of heat stabilizers: C1. Mix 1000g of anhydrous tetrahydrofuran, 100g of hexachlorocyclotriphosphazene, 150g of 4,4'-dihydroxydiphenyl sulfone, and 200g of triethylamine, and react at 50℃ for 10h. Then add 50g of mono-(6-p-toluenesulfonyl)-β-cyclodextrin and graft at 55℃ for 20h to obtain grafted polyphosphazene.

[0025] C2. Take 100g of grafted polyphosphazene and disperse it in 800g of ethanol-water mixed solvent. Add 10g of zinc chloride and 20g of lanthanum nitrate, adjust the pH to 6.5, and perform a coordination reaction at 65℃ for 5h. Add 50g of pentaerythritol, stir at 50℃ for 10h, filter, wash and dry to obtain the intermediate product.

[0026] C3. Take 100g of intermediate product and mix it with 20g of dithiodipropionic acid. Melt and react at 75℃ for 30min. Crush and sieve to obtain a heat stabilizer.

[0027] Manufacturing process of low heat release alloy thermoplastic sheet for aerospace interiors: A1. Chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, and polymethyl methacrylate are put into a high-speed mixer and stirred for 1 minute. Impact modifier, heat stabilizer, lubricant, processing aid, and flame retardant synergist are added and mixed evenly. The mixture is dried at 80°C for 2 hours, then transferred to an automatic mixing device and stirred at low speed for 5 minutes. Finally, it is fed into a twin cone screw extruder for extrusion.

[0028] A2. The extruded sheet enters a three-roll calender, with the upper roll at 80°C, the middle roll at 70°C, and the lower roll at 60°C to create a textured surface. After cooling and setting to room temperature, the edges are trimmed to obtain the finished product.

[0029] Example 2: Low heat release alloy thermoplastic sheet for aerospace interiors, comprising the following raw materials: 1000g chlorinated polyvinyl chloride, 300g polyvinyl chloride, 220g ABS, 100g methyl methacrylate-butadiene-styrene copolymer, 80g polymethyl methacrylate, 100g impact modifier, 70g heat stabilizer, 12g lubricant, 20g processing aid, 30g flame retardant synergist.

[0030] I. Preparation of impact modifier: S1. Take 1000g of deionized water, 35g of sodium dodecylbenzenesulfonate, and 10g of ammonium persulfate and mix them evenly. After purging with nitrogen, heat the mixture to 70℃ and add 350g of mixed monomers (composed of butadiene, styrene, methacryloyloxyethyl phosphate, and vinyltriethoxysilane in a mass ratio of 70:22:5:1). React at a constant temperature for 7h to obtain a nucleus emulsion.

[0031] S2. Add 60g of cage-type polysilsesquioxane and 30g of trimethylolpropane trimethacrylate to 1000g of nuclear emulsion, and keep the reaction at the temperature for 2.5h to obtain a nuclear-encapsulated emulsion.

[0032] S3. Add 220g of shell monomer (composed of methyl methacrylate, glycidyl methacrylate and acrylic acid in a mass ratio of 13:3:1) dropwise to 1000g of core-encapsulated emulsion, continue the reaction for 3.5h, and then demulsify, wash and spray dry to obtain the impact modifier.

[0033] II. Preparation of heat stabilizers: C1. Mix 1000g of anhydrous tetrahydrofuran, 130g of hexachlorocyclotriphosphazene, 200g of 4,4'-dihydroxydiphenyl sulfone, and 250g of triethylamine, and react at 53℃ for 11h. Then add 80g of mono-(6-p-toluenesulfonyl)-β-cyclodextrin and graft at 58℃ for 22h to obtain grafted polyphosphazene.

[0034] C2. Take 100g of grafted polyphosphazene and disperse it in 1200g of ethanol-water mixed solvent. Add 20g of zinc chloride and 30g of lanthanum nitrate, adjust the pH to 6.8, and perform a coordination reaction at 68℃ for 5.5h. Add 100g of pentaerythritol, stir at 53℃ for 11h, filter, wash and dry to obtain the intermediate product.

[0035] C3. Take 100g of intermediate product and mix it with 40g of dithiodipropionic acid. Melt and react at 78℃ for 35min. Crush and sieve to obtain a heat stabilizer.

[0036] Manufacturing process of low heat release alloy thermoplastic sheet for aerospace interiors: A1. Chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, and polymethyl methacrylate are put into a high-speed mixer and stirred for 1.5 min. Impact modifier, heat stabilizer, lubricant, processing aid, and flame retardant synergist are added and mixed evenly. The mixture is dried at 85℃ for 2.5 h, then transferred to an automatic mixing device and stirred at low speed for 8 min. Finally, it is fed into a twin cone screw extruder for extrusion.

[0037] A2. The extruded sheet enters a three-roll calender, where the upper roller is at 85°C, the middle roller at 75°C, and the lower roller at 65°C to create a textured surface. After cooling and setting to room temperature, the edges are trimmed to obtain the finished product.

[0038] Example 3: Low heat release alloy thermoplastic sheet for aerospace interiors, comprising the following raw materials: 1000g chlorinated polyvinyl chloride, 400g polyvinyl chloride, 300g ABS, 150g methyl methacrylate-butadiene-styrene copolymer, 100g polymethyl methacrylate, 150g impact modifier, 100g heat stabilizer, 20g lubricant, 30g processing aid, 40g flame retardant synergist.

[0039] I. Preparation of impact modifier: S1. Take 1000g of deionized water, 50g of sodium dodecylbenzenesulfonate, and 15g of ammonium persulfate and mix them evenly. After purging with nitrogen, heat the mixture to 75℃ and add 450g of mixed monomers (composed of butadiene, styrene, methacryloyloxyethyl phosphate, and vinyltriethoxysilane in a mass ratio of 80:30:8:1). React at a constant temperature for 8 hours to obtain a core emulsion.

[0040] S2. Add 80g of cage-type polysilsesquioxane and 40g of trimethylolpropane trimethacrylate to 1000g of nuclear emulsion, and keep the reaction at the temperature for 3h to obtain a nuclear-encapsulated emulsion.

[0041] S3. Add 300g of shell monomer (composed of methyl methacrylate, glycidyl methacrylate and acrylic acid in a mass ratio of 15:4:1) to 1000g of core-encapsulated emulsion, continue the reaction for 4 hours, and then demulsify, wash and spray dry to obtain the impact modifier.

[0042] II. Preparation of heat stabilizers: C1. Mix 1000g of anhydrous tetrahydrofuran, 150g of hexachlorocyclotriphosphazene, 250g of 4,4'-dihydroxydiphenyl sulfone, and 300g of triethylamine, and react at 55℃ for 12h. Then add 120g of mono-(6-p-toluenesulfonyl)-β-cyclodextrin and graft at 60℃ for 24h to obtain grafted polyphosphazene.

[0043] C2. Take 100g of grafted polyphosphazene and disperse it in 1500g of ethanol-water mixed solvent. Add 30g of zinc chloride and 50g of lanthanum nitrate, adjust the pH to 7, and perform a coordination reaction at 70℃ for 6h. Add 150g of pentaerythritol, stir at 55℃ for 12h, filter, wash and dry to obtain the intermediate product.

[0044] C3. Take 100g of intermediate product and mix it with 60g of dithiodipropionic acid. Melt and react at 80℃ for 40min. Crush and sieve to obtain a heat stabilizer.

[0045] Manufacturing process of low heat release alloy thermoplastic sheet for aerospace interiors: A1. Chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, and polymethyl methacrylate are put into a high-speed mixer and stirred for 2 minutes. Impact modifier, heat stabilizer, lubricant, processing aid, and flame retardant synergist are added and mixed evenly. The mixture is dried at 90°C for 3 hours, then transferred to an automatic mixing device and stirred at low speed for 10 minutes. Finally, it is fed into a twin cone screw extruder for extrusion.

[0046] A2. The extruded sheet enters a three-roll calender, with the upper roll at 90°C, the middle roll at 80°C, and the lower roll at 70°C to create a textured surface. After cooling and setting to room temperature, the edges are trimmed to obtain the finished product.

[0047] Comparative Example 1: Comparative Example 1 differs from Example 1 in that the impact modifier is replaced with an equal mass of methyl methacrylate-butadiene-styrene copolymer, and the remaining steps are exactly the same as in Example 1.

[0048] Comparative Example 2: Comparative Example 2, compared to Example 1, did not add an impact modifier, and the remaining steps were exactly the same as in Example 1.

[0049] Comparative Example 3: Comparative Example 3 differs from Example 1 in that the heat stabilizer is replaced with an equal mass of thiol methyltin heat stabilizer, and the remaining steps are exactly the same as in Example 1.

[0050] Comparative Example 4: Comparative Example 4, compared to Example 1, did not add a heat stabilizer, and the remaining steps were exactly the same as in Example 1.

[0051] The performance of the low heat release alloy thermoplastic sheets for aviation interiors prepared in Examples 1-3 and Comparative Examples 1-4 was tested, and the low heat release alloy thermoplastic sheets for aviation interiors were cut into the dimensions required by the corresponding standards.

[0052] I. Flame retardant performance testing: 1. Limiting Oxygen Index (LOI) Test: Referring to GB / T2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test", a sample with a length of 120 mm, a width of 10 mm, and a thickness of 4 mm was vertically installed in the combustion chamber. The oxygen and nitrogen mixed gas flow was adjusted to a total flow rate of 40 L / min. The top of the sample was ignited, and the combustion behavior of the sample was observed. The minimum oxygen concentration (volume percentage) required to maintain combustion was recorded.

[0053] 2. Vertical Burning Test (UL-94): Referring to GB / T2408-2021 "Determination of Burning Performance of Plastics - Horizontal and Vertical Methods", a sample with a length of 125 mm, a width of 13 mm, and a thickness of 3 mm was vertically fixed on a fixture, with degreased cotton placed on top. The height of the Bunsen burner flame was adjusted to (20 ± 1) mm, and the inner flame height was about 10 mm. The flame was applied for 10 s, and the first afterflame time t1 was recorded. After the flame was removed and the sample self-extinguished, the flame was immediately applied again for 10 s, and the second afterflame time t2 and afterglow time t3 were recorded. Based on t1, t2, t3 and whether the cotton dripped and ignited, the V-0, V-1, or V-2 rating was determined.

[0054] II. Heat release performance testing: Referring to ISO 5660-1:2015 "Tests for reaction to fire—rates of heat release, smoke production and mass loss—Part 1: Cone calorimeter method", a sample measuring 100 mm in length, 100 mm in width and 6 mm in thickness was placed horizontally on a sample holder, with the back wrapped in aluminum foil and a spark igniter mounted on top. The thermal irradiation power was set to 35 kW / m². 2 (Simulating aviation fire heat flow conditions), the sample surface is radiantly heated by a conical heater to ignite the combustion products. Oxygen consumption is measured by an oxygen analyzer, the heat release rate (HRR) is calculated, and the peak heat release rate (PHRR, unit MJ / m³) is recorded. 2 ) and the total heat release (THR, unit MJ / m³) during the entire combustion process. 2 The specific test results are shown in Table 1: Table 1: Thermal Performance Test Table for Low Heat Release Alloy Thermoplastic Sheets for Aerospace Interiors As can be seen from the data in Table 1, the limiting oxygen index of the alloy thermoplastic sheets prepared in Examples 1-3 is all above 41%, reaching the V-0 vertical burning rating. The peak heat release rate and total heat release are significantly lower than those of the comparative examples. The flame retardant properties of Comparative Example 1 (using conventional MBS impact modifier) ​​and Comparative Example 3 (using commercially available methyltin mercaptan heat stabilizer) are significantly reduced, with the oxygen index dropping below 33% and the peak heat release rate increasing to 88 kW / m³. 2 The above results only achieve a V-2 rating. Comparative Example 4 (without heat stabilizer) has the worst flame retardant performance due to severe degradation of CPVC during processing. Comparative Example 2 (without impact modifier) ​​has some flame retardancy, but it is not practical because it cannot meet the mechanical toughness requirements. Example 2 is slightly better than Example 1 and Example 3 in terms of minimum oxygen concentration, peak heat release rate, and total heat release, indicating that the intermediate ratio is the optimal process range.

[0055] III. Mechanical and Tensile Plasticity Testing 1. Elongation at break test: Referring to GB / T1040.3-2006 "Determination of tensile properties of plastics - Part 3: Test conditions for films and sheets", a type 5 dumbbell-shaped specimen was used. The specimen dimensions were: total length ≥ 75 mm, narrow section width (4 ± 0.1) mm, and thickness equal to the original thickness of the sheet (approximately 2-3 mm). The specimen was tested on a universal testing machine at a constant tensile speed of 50 mm / min. The elongation at break was recorded, and the elongation at break was calculated using the following formula: Elongation at break = (Elongation at break / Original gauge length) × 100%.

[0056] 2. Notched impact strength test: Referring to GB / T1843-2008 "Determination of Impact Strength of Plastic Cantilever Beams", a specimen measuring 80 mm in length, 10 mm in width, and 4 mm in thickness, with a V-notch (notch depth 2.54 mm), is fixed on a cantilever beam impact testing machine. The pendulum impact edge is aligned with the back of the notch, the pendulum is released, and the energy absorbed by the specimen at fracture (J) is recorded. The impact strength (kJ / m²) is then calculated. 2 = Absorbed energy / Remaining cross-sectional area at the notch of the sample. The specific test results are shown in Table 2. Table 2: Mechanical Properties Test Table for Low Heat Release Alloy Thermoplastic Sheets for Aerospace Interiors As can be seen from the data in Table 2, the alloy thermoplastic sheets prepared in Examples 1-3 have an elongation at break of over 180% and an impact strength of 25 kJ / m. 2 The above demonstrates excellent tensile thermoforming properties and impact toughness, meeting the requirements for secondary vacuum thermoforming of aerospace interior parts. Specifically, Example 2 exhibits slightly higher elongation at break and impact strength than Examples 1 and 3, further validating the superiority of the intermediate formulation. Comparative Example 2 (without impact modifier) ​​shows an elongation at break of only 15% and an impact strength of only 5 kJ / m. 2 The material is extremely brittle and cannot undergo any secondary molding process. Although the mechanical properties of Comparative Example 1 (using conventional MBS impact modifier) ​​and Comparative Example 3 (using commercially available heat stabilizer) have been improved to some extent, their elongation at break and impact strength are still significantly lower than those of the embodiments of the present invention. Comparative Example 4 (without heat stabilizer) also showed significant deterioration in mechanical properties due to severe thermal degradation during processing. The above data fully demonstrate that the self-made three-layer gradient core-shell impact modifier and supramolecular heat stabilizer of the present invention work synergistically to endow the material with excellent processing and molding performance while maintaining high flame retardancy.

[0057] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A low-heat-release alloy thermoplastic sheet for aerospace interiors, characterized in that, The raw materials include the following parts by weight: 100 parts chlorinated polyvinyl chloride, 20-40 parts polyvinyl chloride, 15-30 parts ABS, 5-15 parts methyl methacrylate-butadiene-styrene copolymer, 5-10 parts polymethyl methacrylate, 5-15 parts impact modifier, 3-10 parts heat stabilizer, 0.5-2 parts lubricant, 1-3 parts processing aid, and 2-4 parts flame retardant synergist; The impact modifier is prepared through the following steps: S1. Add sodium dodecylbenzenesulfonate emulsifier and ammonium persulfate initiator to deionized water, replace with nitrogen, raise the temperature to 65-75℃, add mixed monomers dropwise, react for 6-8 hours to obtain a nucleus emulsion; S2. Add cage-type polysilsesquioxane and trimethylolpropane trimethacrylate dropwise to the core emulsion, and keep the reaction at a warm temperature for 2-3 hours to obtain the core-encapsulated emulsion; S3. Add shell monomers composed of methyl methacrylate, glycidyl methacrylate and acrylic acid dropwise to the core-encapsulated emulsion, continue the reaction for 3-4 hours, demulsify, wash, and spray dry to obtain the impact modifier.

2. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, The heat stabilizer is prepared by the following steps: C1. In anhydrous tetrahydrofuran, hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone were added, and triethylamine was used as an acid-binding agent. The reaction was carried out at 50-55℃ for 10-12 h. Then mono-(6-p-toluenesulfonyl)-β-cyclodextrin was added, and the grafting reaction was carried out at 55-60℃ for 20-24 h to obtain grafted polyphosphazene. C2. The grafted polyphosphazene was dispersed in an ethanol-water mixed solvent, zinc chloride and lanthanum nitrate were added, the pH was adjusted to 6.5-7, and the complexation reaction was carried out at 65-70℃ for 5-6 h. Then pentaerythritol was added, and the mixture was stirred at 50-55℃ for 10-12 h. The intermediate product was obtained by filtration, washing and drying. C3. Mix the intermediate product with dithiodipropionic acid, melt and react at 75-80℃ for 30-40 minutes, then pulverize and sieve to obtain the heat stabilizer.

3. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, In step S1, the mass ratio of deionized water, sodium dodecylbenzenesulfonate emulsifier, ammonium persulfate initiator, and mixed monomers is 100:(2-5):(0.5-1.5):(25-45). The mixed monomers are composed of butadiene, styrene, methacryloyloxyethyl phosphate, and vinyltriethoxysilane in a mass ratio of (60-80):(15-30):(2-8):

1.

4. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, In step S2, the mass ratio of the core emulsion, cage-type polysilsesquioxane, and trimethylolpropane trimethacrylate is 100:(3-8):(1-4).

5. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, In step S3, the mass ratio of the core-encapsulated emulsion to the shell monomer is 100:(15-30), wherein the shell monomer is composed of methyl methacrylate, glycidyl methacrylate and acrylic acid in a mass ratio of (12-15):(2-4):

1.

6. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, In step C1, the mass ratio of anhydrous tetrahydrofuran, hexachlorocyclotriphosphazene, 4,4'-dihydroxydiphenyl sulfone, triethylamine, and mono-(6-p-toluenesulfonyl)-β-cyclodextrin is 100:(10-15):(15-25):(20-30):(5-12).

7. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, In step C2, the mass ratio of grafted polyphosphazene, ethanol-water mixed solvent, zinc chloride, lanthanum nitrate, and pentaerythritol is 1:(8-15):(0.1-0.3):(0.2-0.5):(0.5-1.5).

8. The low heat release alloy thermoplastic sheet for aerospace interiors according to claim 1, characterized in that, The mass ratio of the intermediate product to dithiodipropionic acid in step C3 is 1:(0.2-0.6).

9. A preparation process for preparing the low heat release alloy thermoplastic sheet for aerospace interiors as described in any one of claims 1-8, characterized in that, The preparation process includes the following steps: A1. Chlorinated polyvinyl chloride, polyvinyl chloride, ABS, methyl methacrylate-butadiene-styrene copolymer, and polymethyl methacrylate are put into a high-speed mixer and stirred for 1-2 minutes. Impact modifier, heat stabilizer, lubricant, processing aid, and flame retardant synergist are added and mixed. The mixed material is dried at 80-90℃ for 2-3 hours. The dried material is then put into an automatic mixing device and stirred at low speed for 5-10 minutes. The material mixed a second time is sent into a twin cone screw extruder for extrusion. A2. The extruded hot sheet material enters a three-roll calender, where a leather texture is pressed out according to product requirements. The embossed sheet material enters a cooling and shaping device to cool to room temperature. An edge trimming machine is used to remove the irregular rough edges on both sides of the sheet material to obtain a low-heat-release alloy thermoplastic sheet for aerospace interiors.

10. The preparation process of the low heat release alloy thermoplastic sheet for aerospace interiors according to claim 9, characterized in that, The temperatures of the three rollers in the three-roll calender are controlled as follows: upper roller 80-90℃, middle roller 70-80℃, and lower roller 60-70℃.